Manajemen Kurikulum Berbasis Karakter: Strategi Kepala Sekolah Di Lembaga Pendidikan Islam: Penelitian - Munawwarah; Iis Marsithah; Sri Maharany; Siti Sara Rizkia; Nurlisma (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to identify and explain the strategies of school principals in implementing a character-based curriculum at MA Darussa’adah Cot Tarom. It also describes the process of character curriculum implementation within the school environment. This qualitative research employed data collection techniques including interviews, observation, and document analysis. The participants included the principal, teachers, and students. The findings indicate that the principal plays a strategic role in planning, implementing, and evaluating character education. Strategies applied include integrating Islamic values into the school’s vision, reinforcing religious routines, providing teacher training, building a religious school culture, and conducting ongoing evaluation. The curriculum developed emphasizes not only academic achievement but also the integration of Islamic values to holistically shape student character. This research highlights that character-based curriculum management requires collaborative, participatory, and transformative leadership.